Ethnic Identity of Young Male Representatives of the Nenets Indigenous People of the Russian North - FLOTSKAYA, Natalia; BULANOVA, Svetlana; PONOMAREVA, Maria; KONOPLEVA, Tatiana; FLOTSKIY, Nikolay (DEStech Transactions on Social Science, Education and Human Science, 2019)
Background: The article deals with the problem of ethnic identity with adolescents of Nenets origin. The purpose of our research is to investigate ethnic identity of young Nenets boys— representatives of indigenous people of the Arctic region of Russia—in the course of the adolescence period. Methods: The research was carried out according to the methodology «Types of Ethnic Identity» worked out by G.U. Soldatova and S.V. Ryzhova and it describes development of ethnic identity through ethnonihilism, ethnic indifference, positive ethnic identity, ethnoegoism, ethnoisolation and ethnofanaticism with young boys of Nenets origin aged 12 to 15. Results: The research revealed peculiar features of ethnic identity with the boys of Nenets origin as compared to the boys of Russian origin residing in the Arkhnangelsk region of the Russian Federation.